Determinants of Risk Factors on the Event of Lung Tb - Susanti br Perangin-Angin; Nurmala Hayati Sihombing (Green Publisher Indonesia, 2022)
Pulmonary tuberculosis (TB) is one of the most prevalent infectious diseases in the world. Based on a report by the World Health Organization (WHO, 2012) one third of the world's population, which is around two billion people infected with Mycobacterium Tuberculosis. More than 8 million populations get active TB every year and around 2 million die. More than 90% of TB cases and deaths come from developing countries, one of which is in Indonesia. This research is an observational analytic study with a case control study design that aims to determine the effect of risk factors for pulmonary TB events using a retrospective approach. The results of this study indicate that the most dominant variable TB incidence in high school education cases is down to 45 people (97.8%) and the smallest House Density is 25 people (54.3%) and the most dominant control variable is no comorbidities namely as many as 47 people (97.9%) and the smallest Respondents' House Density fulfilled the requirements of 26 people (56.5%). Factors that significantly influence the incidence of pulmonary tuberculosis are nutritional status (p = 0,000, OR = 31,263), respondent employment (p = 0,000, OR = 21.77), comorbidities (p = 0,000, OR = 0.022), Ventilation (p = 0.001, OR = 4,680) and House Humidity (p = 0,000, OR = 9,625). The results of the study concluded that the variable that most influenced the incidence of pulmonary TB was Nutrition Status (p = 0.002, Exp (B) = 2.334).